Variability in Soil Chemical Quality in Traffic-dependent Zones within Field Headlands. Issue 19 (28th October 2021) - Metzger, Konrad; Zhang, Chaosheng; Ward, Mark; Daly, Karen
ABSTRACT: There is increased stress on soil and crop quality caused by machinery traffic during field operations in tillage systems, especially the area where the machinery turns, known as the headlands. While the influence of traffic on soil physical quality is understood, the impact on soil chemical quality and soil fertility is less so. Furthermore, correcting soil fertility and chemical quality in fields under cereal tillage requires strategic sampling due spatial variability, specifically in headlands. Using a simplified sampling strategy, the objective of this study was to examine the variability in soil chemical quality within traffic-dependent zones in the headland. In a case-study in Ireland, 41 fields under tillage were surveyed, and soil sampling zones delineated within headlands based on typical field traffic patterns. Soil phosphorus (P), potassium (K), lime requirement (LR), pH and organic matter (%OM) were measured at two depths. Elevated values of major nutrients (P, K) were recorded around the main headland tramline. Using a generalized linear mixed model, significant differences in P, K, LR and pH were found between headland zones, whereas %OM values did not vary significantly. In addition to laboratory analyses, predictions from mid-infrared spectroscopy (MIR) models resulted in similar patterns in %OM and LR with comparable statistical significance, which highlights the potential of MIR as an alternative to lab analysis of soil in traffic-dependent headland zones. Sampling headland zones to determine soil chemical quality coupled with the application of MIR for rapid soil analysis will improve decision support for soil management in tillage systems.